2019
DOI: 10.1172/jci.insight.128034
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor enhances influenza-associated mortality in mice

Abstract: Conflict of interest: RB is a coinventor on patents describing the therapeutic utility of anti-MIF (US9139877B2) and MIF antagonists (US9221903B2) and has received royalty payments in the past.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…It has been suggested that the level of MIF expression can be regarded as a sensitive and effective biochemical indicator in the early diagnosis of ARDS [19]. Also, MIF has been identified in some viral infections like influenza, Human Immunodeficiency Virus (HIV), H5N1 virus and dengue virus infections [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the level of MIF expression can be regarded as a sensitive and effective biochemical indicator in the early diagnosis of ARDS [19]. Also, MIF has been identified in some viral infections like influenza, Human Immunodeficiency Virus (HIV), H5N1 virus and dengue virus infections [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Besides parasitic and bacterial models, in which MIF was shown to drive/mediate infection-related immune-pathological outcomes, analogous MIF-mediated effects were also documented to occur during experimental viral infections. For example, influenza A virus (IAV) infections in Mif -/- mice resulted in less inflammation, viral load and mortality compared to WT control mice and similar features were recorded with antibody-mediated MIF blockade ( 133 ). Conversely, transgenic mice overexpressing MIF in alveolar epithelial cells had higher inflammation, viral load, and mortality ( 133 ).…”
Section: Macrophage Migration Inhibitory Factor (Mif)mentioning
confidence: 90%
“…For example, influenza A virus (IAV) infections in Mif -/- mice resulted in less inflammation, viral load and mortality compared to WT control mice and similar features were recorded with antibody-mediated MIF blockade ( 133 ). Conversely, transgenic mice overexpressing MIF in alveolar epithelial cells had higher inflammation, viral load, and mortality ( 133 ). Finally, treatment of human lung epithelial cells with recombinant human MIF promoted the spread of IAV in vitro ( 133 ).…”
Section: Macrophage Migration Inhibitory Factor (Mif)mentioning
confidence: 90%
“…The established researches identified and elucidated two signal pathways of mitophagy: ubiquitin- (Ub-) dependent and Ub-independent (receptor-mediated mitophagy) [ 31 ]. Some study holds that MIF induces mitophagy via BNIP3-mediated pathway, an Ub-independent manner of mitophagy [ 32 ], while some other holds that MIF is the regulator of PINK1/Parkin-mediated mitophagy, the most well-defined Ub-mediated pathway of mitophagy [ 33 ]. The results of our prior and current studies elucidated that overload compression-associated mitophagy was related to the PINK1/Parkin-mediated macroautophagy [ 5 ].…”
Section: Discussionmentioning
confidence: 99%